Calreticulin: Challenges Posed by the Intrinsically Disordered Nature of Calreticulin to the Study of Its Function - Varricchio, Lilian; Falchi, Mario; Dall'Ora, Massimiliano; De Benedittis, Caterina; Ruggeri, Alessandra; Uversky, Vladimir N.; Migliaccio, Anna Rita (Frontiers in Cell and Developmental Biology, 2017)
Calreticulin is a Ca2+-binding chaperone protein, which resides mainly in the endoplasmic reticulum but also found in other cellular compartments including the plasma membrane. In addition to Ca2+, calreticulin binds and regulates almost all proteins and most of the mRNAs deciding their intracellular fate. The potential functions of calreticulin are so numerous that identification of all of them is becoming a nightmare. Still the recent discovery that patients affected by the Philadelphia-negative myeloproliferative disorders essential thrombocytemia or primary myelofibrosis not harboring JAK2 mutations carry instead calreticulin mutations disrupting its C-terminal domain has highlighted the clinical need to gain a deeper understanding of the biological activity of this protein. However, by contrast with other proteins, such as enzymes or transcription factors, the biological functions of which are strictly defined by a stable spatial structure imprinted by their amino acid sequence, calreticulin contains intrinsically disordered regions, the structure of which represents a highly dynamic conformational ensemble characterized by constant changes between several metastable conformations in response to a variety of environmental cues. This article will illustrate the Theory of calreticulin as an intrinsically disordered protein and discuss the Hypothesis that the dynamic conformational changes to which calreticulin may be subjected by environmental cues, by promoting or restricting the exposure of its active sites, may affect its function under normal and pathological conditions.